UNDERSTANDING THE PORTRAYAL OF TOXIC CHARACTERIZATION IN TAMIL CINEMA FROM A GENDER LENS - S., Shridevi; Jayalakshmi; Raja, N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The film is an integral part of human lives. The potential of film is beyond the functions of the mass media which are information, education and entertainment. The film media act as an agent of cultural transformation, shaping the perception, forming the ideologies and the like. Watching films with family, friends, and well-wishers has been a channel of emotional association. Watching films with family and friends gives us the liberty to explore our inner self and to share our views about the films and its content with each other. The concept of masculinity and feminity in films is not new but it has its roots in the context of gender and culture. This is a socio-cultural idea which conditions a man and woman with stereo-typical behaviours in order to fit in a predetermined cultural framework. The term toxic refers to the concepts which are harmful to the human wellbeing. This research throws light on the investigation of toxic masculinity and feminity traits and the understanding of these traits among the college going students through films. According to Live Mint (2022) It is revealed that, in the post pandemic period the frequency of theatre goers has increased. The young adults in the age group of 18-29 are the frequent film viewers. Based on the research articles, it is found that in India 15% of the people watch films in the theatre one time in a week. 8% of the people mentioned that they visit the theatre fifteen days once. Understanding the concept of toxic masculinity and feminity in films by the students is the need of the hour. Students are inculcated with the ideologies, behaviours, body language with what they see in the silver screen which subsequently is reflected in their relationships with friends and family members. In this regard, the researchers made an attempt to investigate these concepts from the student’s perspective.